2016
DOI: 10.1002/2015jd024304
|View full text |Cite
|
Sign up to set email alerts
|

An intensified hydrological cycle in the simulation of geoengineering by cirrus cloud thinning using ice crystal fall speed changes

Abstract: Proposals to geoengineer Earth's climate by cirrus cloud thinning (CCT) potentially offer advantages over solar radiation management schemes: amplified cooling of the Arctic and smaller perturbations to global mean precipitation in particular. Using an idealized climate model implementation of CCT in which ice particle fall speeds were increased 2×, 4×, and 8× we examine the relationships between effective radiative forcing (ERF) at the top of atmosphere, near-surface temperature, and the response of the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 61 publications
3
22
0
Order By: Relevance
“…2a) as already noted by Jackson et al (2016). This is because the cirrus CRE always decreases by about 30 % when doubling the IC sedimentation velocity, i.e.…”
Section: Increased Sedimentation Velocitysupporting
confidence: 78%
See 1 more Smart Citation
“…2a) as already noted by Jackson et al (2016). This is because the cirrus CRE always decreases by about 30 % when doubling the IC sedimentation velocity, i.e.…”
Section: Increased Sedimentation Velocitysupporting
confidence: 78%
“…As it is computationally demanding to simulate the detailed cirrus microphysical processes, climatic responses of seeding are often represented by increasing the IC sedimentation velocity in cirrus clouds (Muri et al, 2014;Crook et al, 2015;Jackson et al, 2016). Increasing the IC sedimentation velocity can, analogous to seeding, decrease the amount of cirrus cloud cover, ice water content (IWC), and ice crystal number concentration (ICNC).…”
Section: B Gasparini Et Al: Seeding Vs Sedimentationmentioning
confidence: 99%
“…Numerous modeling studies have demonstrated the effect of stratospheric aerosol geoengineering on temperature and hydrological cycle [ National Research Council , , and references therein], which is further illustrated by the imperfect analog of volcanic eruption [ Rasch et al ., ]. Our simulated climate response to CCT geoengineering is in broad agreement with previous studies in that CCT reduces CO 2 ‐induced warming without substantially weakening the global hydrological cycle [ Muri et al ., ; Kristjánsson et al ., ; Crook et al ., ; Jackson et al ., ]. However, only a few studies have evaluated the climate effect of CCT, which merits further modeling studies preferably with improved representation of cloud microphysics [ Bardeen et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Another type of studies used a prescribed increased sedimentation velocity of ice crystals as proxy for seeding (Crook et al, ; Jackson et al, ; Muri et al, ). This approach can reproduce surface climate responses to seeding but is unable to capture the changes in cloud microphysical processes that occur when considering seeding aerosol in a cirrus formation parameterization (Gasparini et al, ).…”
Section: Introductionmentioning
confidence: 99%